Pengaruh Budaya Organisasi dan Disiplin Kerja Terhadap Kinerja Karyawan pada Bank Umum Syariah dengan Lingkungan Kerja sebagai Variabel Moderasi - Armilda Sandraningtyas; Toto Suharto; Ridwan Widagdo (Fakultas Ekonomi dan Bisni Islam UIN Siber Syekh Nurjati Cirebon, 2025)
This research aims to measure and analyze the influence of organizational culture and work discipline on employee performance at Sharia Commercial Banks in Kuningan Regency, with the work environment as a moderating variable. The method used in this research is hypothesis testing with a quantitative approach. The population in this study were all employees of Sharia Commercial Banks in Kuningan Regency. Samples were taken using the total sample technique. The number of samples taken and used in this research was 35 employees. Data collection techniques use questionnaires distributed directly. The data analysis method used is Moderated Regression Analysis with the help of SPSS software version 22. The research results show that organizational culture has a positive and significant effect on employee performance, with a calculated t value = 3.420 > t table and a significance level = 0.002 < 0.05. Work discipline has a positive and significant effect on employee performance, with a calculated t value = 4.809 > t table and a significance level of 0.000 < 0.05. The work environment is unable to moderate the influence of organizational culture on employee performance, with a parameter coefficient value (β) of 0.007 and a significance level = 0.307 > 0.05. The work environment negatively moderates (weakens) the influence of organizational culture on employee performance, with a parameter coefficient value (β) of -0.016 and a significance level = 0.048 <0.05.